Effects of salt mixtures on in vitro digestion of sodium-substituted myofibrillar protein gel: Disintegration and gastric juice diffusion - Haibo Shi; Haoqi Zhang; Chenxi Liu; Guofu Yi; Yumin Zhang; Jiabao Zheng; Yongxin Teng; Shuangjie Zhu; Rui Jiao; Weizheng Sun (Food Research International, 2026)

Incorporating dynamic ozone stress and parameter optimization into the BEPS model for improved GPP simulation - Jian Wang; Yuling Du; Jibo Yue; Tianxiang Cui; Yumin Chen; Lin Sun; Lei Shi (Ecological Modelling, 2026)

A multifunctional PPy/GO/PVDF photothermal membrane for solar-driven water purification coupled with dye desalination - Yang Li; Yumin Sun; Xinxin Cao; Xutong Han; Hailiang Liu (Desalination, 2026)

High-throughput nucleic acid extraction using a pipette-tip annular magnetic separator integrated with real-time fluorescent RPA for rapid detection of Burkholderia gladioli pv. cocovenenans - Jiali Wang; Yuting Su; Yaru Chen; Lei Tang; Dongmei Li; Wenchao Du; Yumin Shen; Fangfang Zhou; Hong Duan; Baoguo Sun; Gang Chen; Lingyan Zheng (Food Bioscience, 2026)

Pore structure evolution in organic-rich shale during thermal maturation: Insights from hydrous pyrolysis of two lacustrine kerogens - Fengtian Bai; Lee A. Stevens; Clement N. Uguna; Wei Li; Will Meredith; Colin E. Snape; Christopher H. Vane; Yumin Liu; Chenggong Sun (Fuel, 2026)

Bidirectional interfacial polymerization-architected nanoporous graphene-polyamide nanofilms for efficient antibiotic separation - Yumin Sun; Yongbo Yang; Sha Liang; Yihang Zhang; Qinglin Huang; Xutong Han; Changfa Xiao; Wei Li; Kaikai Chen; Xianhui Li; Yang Yang; Hailiang Liu (Chemical Engineering Journal, 2026)

Intensified anthropogenic activities dominate the spatiotemporal dynamics of antibiotic resistance genes in lake ecosystems - Yunchao Liu; Yumin Gong; Yida Cheng; Haohan Zhang; Min Qiao; Jianhong Liang; Ruibo Sun; Shiqin Wang; Jin Liu; Fenghua Wang (Environmental Research, 2026)

Mechanism study of phthalate exposure promoting endometriosis: Based on the ferroptosis perspective - Haiyang Wang; Fengping Wu; Yifan Li; Haiyan Chen; Xinxin Wang; Zhonghua Sun; Ning Gu; Yumin Zhu (Journal of Hazardous Materials, 2026)

Poly(deep eutectic solvent)@MOF-801 for technical surveillance of carbaryl: Pesticide residue safety control strategy - Xicheng He; Yumin Yang; Ying Cao; Ziming Wang; Haixiang Li; Zhiliu Liu; Yan Wang; Fengyun Li; Qian Zhang; Abdulla Yusuf; Feiran Li; Mi Hu; et al. (Journal of Environmental Management, 2026)

Correction: Uncovering the molecular basis of high morphinan product efficiency in opium poppy through Multi-omics integrated analysis with multi-capsules - Yumin Huang; Mao Sun; Wuhu Gong; Yifeng Liu; Yimeng Cheng; Lijuan Yuan; Yuanming Wu (Plant Molecular Biology, 2026)

Uncovering the molecular basis of high morphinan product efficiency in opium poppy through Multi-omics integrated analysis with multi-capsules - Yumin Huang; Mao Sun; Wuhu Gong; Yifeng Liu; Yimeng Cheng; Lijuan Yuan; Yuanming Wu (Plant Molecular Biology, 2026)

Elucidating the vertical migration of antibiotic resistance genes in soils amended with swine manure and irrigated with wastewater - Yumin Gong; Yunchao Liu; Yida Cheng; Bingxia Liu; Min Qiao; Ruibo Sun; Bin Guo; Jin Liu; Fenghua Wang (Applied Soil Ecology, 2026)

A novel deep learning system for STEMI prognostic prediction from multi-sequence cardiac magnetic resonance - Yifan Chen; Meng Jiang; Chao Xia; Hang Zhao; Panpan Ke; Sheng Chen; Heng Ge; Keran Li; Xu Wang; Yufei Wang; Yezi Chai; Qiming Liu; et al. (Science Bulletin, 2025)

Superhydrophobic through-pore PI/PTFE aerogels enable high-temperature W/O emulsion separation - Kaixuan Sun; Yumin Sun; Huanru Wang; Pu Zhang; Yanyang Wang; Xutong Han; Xiongfei Du; Qinglin Huang (Journal of Environmental Chemical Engineering, 2025)

Boosting methanol productivity from plasma catalysis CO2 hydrogenation over Cu-based catalysts in a dielectric barrier discharge reactor via metal and support modifications - Yumin Chen; Longkun Sun; Xiaoqi Du; Bingxin Zhu; Yongheng Dong; Yang Liu; Bo Yu; Li Yang; Yongchun Zhao (Chemical Engineering Journal, 2025)

Zircon records water-fluxed melting in origin of W-rich magma: Insights from the Yangchuling porphyry W Mo deposit, South China - Qingqing Yin; Juxing Tang; Jingjing Dai; Inna Safonova; Faqiao Li; Hao Sun; Yumin Xu; Xinkui Xiang; Jinling Xie; Baoping Gan; Bohao Yin; Zhongchao Zheng; et al. (Lithos, 2025)

Ceramic fiber aerogels based flexible solar steam generators enabling efficient thermal localization and high salt resistance - Yun Jiang; Yumin Liu; Lin Li; Zhibin Li; Pengzhang Li; Xianshu Qiao; Wenyan Zhao; Chuanjin Tian; Weiwei Sun; Yanhao Dong; Zhipeng Xie; Chang-An Wang (Desalination, 2025)

Insights into interaction mechanism of plasma, catalysis and thermal processes during toluene oxidation in a packed dielectric barrier discharge plasma reactor - Yumin Chen; Bingxin Zhu; Longkun Sun; Xiaoqi Du; Chengjing Shi; Yongheng Dong; Yanyan Ren; Xinyu Wang; Yang Liu; Huaichun Zhou (Fuel, 2025)

Eu-O-P bond-mediated suppression of ligand-to-metal charge transfer in metal-organic frameworks for ratiometric fluorescent detection of ethephon - Zhikun Zhang; Liwei Bai; Heli Tian; Dingran Zhang; Chenxia Sun; Zhengjie Li; Kunjie Li; Yumin Liu; Yongqi Hu; Jilong Han; Qingju Liu (Chemical Engineering Journal, 2025)

Effects of pelletizing pressure and particle size on flame characteristics and potassium release in volatile combustion of biomass pellets - Xinyu Wang; Teng Ma; Jianchao Sun; Lai Jiang; Yang Liu; Bo Yu; Yumin Chen; Ming Zhai; Huaichun Zhou (Biomass and Bioenergy, 2025)

Voclosporin promotes neurological function recovery by inhibiting inflammation and maintaining blood–brain barrier integrity following rtPA reperfusion after MCAO in mice - Yangmin Zheng; Shubei Ma; Wei Sun; Feng Yan; Yumin Luo (Inflammopharmacology, 2025)

Design of multi-epitope chimeric phage nanocarrier vaccines for porcine deltacoronavirus - GuoQing Zhao; YuMin Zhang; Yan Li; ShiDan Zhang; ShengJing Jiao; XiaoYan Zeng; JingJiao Ma; YuQiang Cheng; HengAn Wang; YaXian Yan; JianHe Sun; Pan Tao; et al. (Veterinary Microbiology, 2025)

Nanoporous graphene thin films for ultra-fast dye/salt separation under low pressure - Huanyi Xiong; Yumin Sun; Qian Zhang; Qinglin Huang; Kaikai Chen; Changfa Xiao; Xianhui Li; Hailiang Liu (Chemical Engineering Journal, 2025)

Revealing the synergistic effect of bulk and surface co-doped boron on TiO2 for enhanced photocatalytic H2 evolution - Bo Li; Hongshun Zheng; Tong Zhou; Baoye Zi; Qingjie Lu; Dequan Li; Mao Zhang; Zhishi Qiu; Zhongge Luo; Yumin Zhang; Bin Xiao; Mingpeng Chen; et al. (Chemical Engineering Journal, 2024)

Shining light on atomic vacancies in electrocatalysts for boosted water splitting - Mingpeng Chen; Huachuan Sun; Qingjie Lu; Dequan Li; Di Liu; Tong Zhou; Baoye Zi; Hongshun Zheng; Bin Xiao; Tianwei He; Jianhong Zhao; Yumin Zhang; et al. (Chemical Engineering Journal, 2024)

Structure and Evolution of Multi-Trend Faults in BZ19-6 Buried Hill of the Bohai Bay Basin, Eastern China - Rui Lou; Yonghe Sun; Fujie Jiang; Yumin Liu; Tian Gao (Journal of Marine Science and Engineering, 2024)
Defining the structure and evolution of multi-trend faults is critical for analyzing the accumulation of hydrocarbons in buried hills. Based on high-resolution seismic and drilling data, the structural characteristics and evolutionary mechanism of multi-trend faults were investigated in detail through the structural analysis theory and quantitative calculations of fault activity, allowing us to determine the implication that fault evolution exerts on hydrocarbon accumulation in the BZ19-6 buried hill. There are four kinds of strike faults developed on the buried hill: SN-, NNE-, NE–ENE-, and nearly EW-trending, which experienced the Mesozoic Indosinian, Yanshan, and Cenozoic Himalayan tectonic movements. During the Indosinian, the BZ19-6 was in a SN-oriented compressional setting, with active faults composed of SN-trending strike-slip faults (west branch of the Tanlu fault zone) and near EW-trending thrust faults (Zhang-peng fault zone). During the Yanshanian, the NNE-trending normal faults were formed under the WNW–ESE tensile stress field. Since the Himalayan period, the BZ19-6 buried hill has evolved into the rifting stage. In rifting stage Ⅰ, all of the multi-trend pre-existing faults were reactivated, and the EW-trending thrust faults became normal faults due to negative inversion. In rifting stage II, a large number of NE–ENE-trending normal faults were newly formed in the NW–SE-oriented extensional setting, which made the structure pattern more complicated. In rifting stage III, the buried hill entered the post-rift stage, with only part of the NNE- and NE–ENE-trending faults continuously active. Multi-trend faults are the result of the combination of various multi-phase stress fields and pre-existing structures, which have great influence on the formation of tectonic fractures and then control the distribution of high-quality reservoirs in buried hills. The fractures controlled by the NNE- and EW-trending faults have higher density and scale, and fractures controlled by NE–ENE trending faults have stronger connectivity and effectiveness. The superposition of multi-trend faults is the favorable distribution of high-quality reservoirs and the favorable accumulation area of hydrocarbon.

Enhanced mixing of north Pacific deep western-boundary currents after Panama seaway closure - Xiaodong Jiang; Xiaoming Sun; James R. Hein; Xuefa Shi; Yao Guan; Yumin Chou; Weijie Zhang; Qingsong Liu (Global and Planetary Change, 2024)

Anisotropic topological scaffolds synergizing non-invasive wireless magnetic stimulation for accelerating long-distance peripheral nerve regeneration - Qi Han; Wenchao Guan; Shaolan Sun; Tiantian Zheng; Linliang Wu; Hongxia Gao; Yaqiong Liu; Yumin Yang; Guicai Li (Chemical Engineering Journal, 2024)

Reaction mechanism investigation on Plasma-Assisted steam reforming of toluene based on emission spectrum analysis and kinetic simulation - Chengjing Shi; Yumin Chen; Yongheng Dong; Wenjing Yue; Longkun Sun; Xinyu Wang; Yang Liu; Huaichun Zhou (Chemical Engineering Journal, 2024)

Efficacy and safety of high-frequency repetitive transcranial magnetic stimulation (rTMS) for migraine: a meta-analysis of randomized controlled trials - Yumin Jiang; Chen Yuan; Pengpeng Sun; Changjia Li; Ling Wang (Acta Neurologica Belgica, 2024)

Transformation of 6:6 PFPiA in the gut of Xenopus laevis: Synergistic effects of CYP450 enzymes and gut microflora - Tianxu Zhang; Yang Lyu; Meng Yuan; Menglin Liu; Yumin Zhu; Binbin Sun; Wenjue Zhong; Lingyan Zhu (Journal of Hazardous Materials, 2024)

Phage cocktail superimposed disinfection: A ecological strategy for preventing pathogenic bacterial infections in dairy farms - Yibing Xue; Ya Gao; Mengting Guo; Yumin Zhang; Guoqing Zhao; Lu Xia; Jingjiao Ma; Yuqiang Cheng; Hengan Wang; Jianhe Sun; Zhaofei Wang; Yaxian Yan (Environmental Research, 2024)

Multidimensional nanochannel design and regulation of ultra-thin GOQDs-AGQDs composite membranes - Hao Cui; Wei Zhao; Hailiang Liu; Yumin Sun; Huanyi Xiong; Qinglin Huang; Kaikai Chen (Chemical Engineering Journal, 2024)

Preparation and performance of magnetic carbon nanotubes modified PVC substrate composite nanofiltration membranes - Jiamin Li; Hailiang Liu; Yang Qin; Yumin Sun; Chaorui Wang; Jian Zhao; Qinglin Huang; Changfa Xiao (Journal of Environmental Chemical Engineering, 2024)

Defluorination of perfluorooctanoic acid and perfluorooctane sulfonic acid by heterogeneous catalytic system of Fe-Al2O3/O3: Synergistic oxidation effects and defluorination mechanism - Yumin Zhang; Zhijie Guan; Xiaojian Liao; Yu Huang; Zhenhua Huang; Zhihua Mo; Baixuan Yin; Xingfan Zhou; Wencan Dai; Jialin Liang; Shuiyu Sun (Science of The Total Environment, 2024)

Renewable cycle for CO2 decomposing by liquid metals at ambient conditions - Liangfei Duan; Zhou Tong; Zhongge Luo; Tianwei He; Mingpeng Chen; Jin Zhang; Huachuan Sun; Yumin Zhang; Jianhong Zhao; Qingju Liu (Journal of Cleaner Production, 2024)

Ru single-atom regulated Ni(OH)2 nanowires coupled with FeOOH to achieve highly efficient overall water splitting at industrial current density - Boxue Wang; Huachuan Sun; Mingpeng Chen; Tong Zhou; Hongshun Zheng; Mengling Zhang; Bin Xiao; Jianhong Zhao; Yumin Zhang; Jin Zhang; Qingju Liu (Chemical Engineering Journal, 2024)

Field parameters investigation of CO2 splitting in atmospheric DBD plasma by multi-physics coupling simulation and emission spectroscopy measurements - Wenjie Huang; Wenjing Yue; Yongheng Dong; Qiancheng Lu; Chengjing Shi; Longkun Sun; Yuanshu Shi; Yumin Chen; Yongchun Zhao (Fuel, 2023)

Cu and Pd dual-single-atoms anchored titanium dioxide for remarkable photocatalytic H2 evolution efficiency - Tong Zhou; Tianping Lv; Bin Xiao; Liangfei Duan; Qingjie Lu; Baoye Zi; Hongshun Zheng; Mingpeng Chen; Jin Zhang; Huachuan Sun; Yumin Zhang; Longzhou Zhang; et al. (Chemical Engineering Journal, 2023)

Alteration of genome-wide DNA methylation in non-uranium miners induced by high level radon exposure - Pinhua Zhang; Yunyun Wu; Chunnan Piao; Yanchao Song; Yanfang Zhao; Yumin Lyu; Quanfu Sun; Jianxiang Liu (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

Chemical vapor deposition of transparent superhydrophobic anti-Icing coatings with tailored polymer nanoarray architecture - Xiaocheng Huang; Min Sun; Xiao Shi; Junli Shao; Minghui Jin; Wenna Liu; Ruhao Zhang; Shuangwu Huang; Yumin Ye (Chemical Engineering Journal, 2023)

Autonomous navigation for lunar final approach based on gravity gradient measurements - Pei Chen; Xuejian Mao; Xiucong Sun; Yumin Lai (Advances in Space Research, 2023)

Molecular characterization of myosin heavy chain and its involvement in muscle growth and development in the Yesso scallop Patinopecten yessoensis - Yumin Yang; Liqing Zhou; Tao Yu; Yanxin Zheng; Biao Wu; Zhihong Liu; Xiujun Sun (Aquaculture, 2023)

Salsolinol Induces Parkinson’s Disease Through Activating NLRP3-Dependent Pyroptosis and the Neuroprotective Effect of Acteoside - Yumin Wang; Shuang Wu; Qiang Li; Weihong Lang; Wenjing Li; Xiaodong Jiang; Zhirong Wan; Huiyan Sun; Hongquan Wang (Neurotoxicity Research, 2022)

Effects of Vegetation Restoration on Soil Enzyme Activity in Copper and Coal Mining Areas - Hui Sun; Jianfeng Zhang; Rongjia Wang; Zongtai Li; Shiyong Sun; Guanghua Qin; Yumin Song (Environmental Management, 2021)

MiR-367 alleviates inflammatory injury of microglia by promoting M2 polarization via targeting CEBPA - Hui Pei; Qian Peng; Shewei Guo; Yulei Gu; Tongwen Sun; Dong Xu; Yumin Jiang; Jiafeng Xie; Luanluan Zhang; Zhiqiang Zhu (In Vitro Cellular & Developmental Biology - Animal, 2020)
MiR-367 was reported to regulate inflammatory response of microglia. CCAAT/enhancer-binding protein α (C/EBPA) could mediate microglia polarization. In this study, we explored the possible roles of miR-367 and CEBPA in intracerebral hemorrhage (ICH). ICH and normal specimens were obtained from the tissue adjacent to and distant from hematoma of ICH patients, respectively. Microglia were isolated and identified by immunofluorescence. The isolated microglia were treated with erythrocyte lysate and randomly divided into 8 groups using different transfection reagents. The transfection efficiency of miR-367 was determined by qRT-PCR. The expressions of M1 and M2 microglia markers were detected by Western blotting. The relationship between CEBPA and miR-367 was confirmed by dual luciferase reporter system. Flow cytometry was performed to determine the level of apoptosis in the cells transfected with miR-367 and CEBPA in erythrocyte lysate–treated microglia. We found that miR-367 expression level was downregulated in ICH specimens. Erythrocyte lysate–treated microglia was successfully established using erythrocyte lysate, as decreased miR-367 expression was observed. Overexpression of miR-367 could significantly decrease the expressions of MHC-ІІ, IL-1β, and Bax, reduced apoptosis rate, and increased the expressions of CD206, Bal-2, and Arg-1 in erythrocyte lysate–treated microglia. CEBPA was proved to be a direct target for miR-367, which could inhibit microglia M2 polarization and increase apoptosis rate. However, in the presence of both CEBPA and miR-367 mimic, the protein and mRNA expressions of CEBPA were decreased, leading to promoted microglia M2 polarization and a decreased apoptosis rate. MiR-367 regulates microglia polarization by targeting CEBPA and is expected to alleviate ICH-induced inflammatory injury.

NOD1 inhibits proliferation and enhances response to chemotherapy via suppressing SRC-MAPK pathway in hepatocellular carcinoma - Xiaomin Ma; Yumin Qiu; Lihui Zhu; Yunxue Zhao; Yueke Lin; Dapeng Ma; Zhenzhi Qin; Caiyu Sun; Xuecheng Shen; Tao Li; Lihui Han (Journal of Molecular Medicine, 2020)

Aerial image mosaicking based on the 6-DoF imaging model - Yumin Tian; Aifeng Sun; Nan Luo; Yun Gao (International Journal of Remote Sensing, 2020)

Seam-line determination via minimal connected area searching and minimum spanning tree for UAV image mosaicking - Yumin Tian; Aifeng Sun; Di Wang (International Journal of Remote Sensing, 2018)

Interval joint-probabilistic chance-constrained programming with two-side multi-randomness: an application to energy-environment systems management - Gongchen Li; Wei Sun; Ying Lv; Guanhui Cheng; Yumin Chen; Guo H. Huang (Stochastic Environmental Research and Risk Assessment, 2018)

AMPK Negatively Regulates Peripheral Myelination via Activation of c-Jun - Xiaoyu Liu; Su Peng; Yahong Zhao; Tingting Zhao; Meihong Wang; Lan Luo; Yumin Yang; Cheng Sun (Molecular Neurobiology, 2017)

Chitosan Degradation Products Promote Nerve Regeneration by Stimulating Schwann Cell Proliferation via miR-27a/FOXO1 Axis - Yongjun Wang; Yahong Zhao; Cheng Sun; Wen Hu; Jing Zhao; Guicai Li; Luzhong Zhang; Mei Liu; Yan Liu; Fei Ding; Yumin Yang; Xiaosong Gu (Molecular Neurobiology, 2016)

LNX (Ligand of Numb-protein X) interacts with RhoC, both of which regulate AP-1-mediated transcriptional activation - Dan Zheng; Yaqiong Sun; Shaohua Gu; Chaoneng Ji; Wei Zhao; Yi Xie; Yumin Mao (Molecular Biology Reports, 2010)

Expression and characterization of HSPC129, a RNA polymerase II C-terminal domain phosphatase - Hui Qian; Chaoneng Ji; Shuo Zhao; Jinzhong Chen; Mei Jiang; Yong Zhang; Mi Yan; Dan Zheng; Yaqiong Sun; Yi Xie; Yumin Mao (Molecular and Cellular Biochemistry, 2007)

Molecular cloning and characterization of AAAS-V2, a novel splice variant of human AAAS - Xin Li; Chaoneng Ji; Jiefeng Gu; Jian Xu; Zhe Jin; Liyun Sun; Xianqiong Zou; Yun Lin; Ruping Sun; Peng Wang; Shaohua Gu; Yumin Mao (Molecular Biology Reports, 2005)

A Novel Zinc Finger Gene ZNF468 with Two Co-Expressional Splice Variants, ZNF468.1 and ZNF468.2 - Liyun Sun; Shaohua Gu; Ni Li; Dan Zheng; Yaqiong Sun; Dan Li; Chaoneng Ji; Kang Ying; Yi Xie; Yumin Mao (Biochemical Genetics, 2005)

Cloning and characterization of a novel human phosphatidic acid phosphatase type 2, PAP2d, with two different transcripts PAP2d_v1 and PAP2d_v2 - Liyun Sun; Shaohua Gu; Yaqiong Sun; Dan Zheng; Qihan Wu; Xin Li; Jianfeng Dai; Jianliang Dai; Chaoneng Ji; Yi Xie; Yumin Mao (Molecular and Cellular Biochemistry, 2005)

Molecular Cloning and Characterization of a Novel Human C4orf13 Gene, Tentatively a Member of the Sodium Bile Acid Cotransporter Family - Xianqiong Zou; Dianzuo Wang; Guanzhou Qiu; Chaoneng Ji; Feng Jin; Maoqing Wu; Huarui Zheng; Xin Li; Liyun Sun; Yu Wang; Rong Tang; Robert Chunhua Zhao; et al. (Biochemical Genetics, 2005)

Cloning and characterization of a novel human homolog* of mouse U26, a putative PQQ-dependent AAS dehydrogenase - Liu Wang; Chaoneng Ji; Yiren Xu; Jian Xu; Jianfeng Dai; Qihan Wu; Maoqing Wu; Xianqiong Zou; Liyun Sun; Shaohua Gu; Yi Xie; Yumin Mao (Molecular Biology Reports, 2005)

Molecular cloning and characterization of a novel human protein phosphatase 2C cDNA (PP2C ε) - Feng Jin; Chaoneng Ji; Lingfeng Liu; Jianfeng Dai; Shaohua Gu; Xianfei Sun; Yi Xie; Yumin Mao (Molecular Biology Reports, 2004)